2018
DOI: 10.1136/sextrans-2017-053350
|View full text |Cite
|
Sign up to set email alerts
|

Modelling individual vulnerability to sexually transmitted infections to optimise intervention strategies: analysis of surveillance data from Kalamazoo County, Michigan, USA

Abstract: The results provide evidence that individual vulnerability to STI has some dependency on individual contextual (race) and exogenous factors at the neighbourhood level such as SES, regardless of that individual's personal history of infection. We suggest place-based intervention strategies be adopted for planning STI interventions instead of current universal screening of at-risk populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Each chlamydia case in the MDSS was assigned a unique patient identifier. For patients with multiple reported chlamydia infections, a case was considered new if the second reported positive test occurred more than 14 days after the first positive test (Bernstein et al, 2004;Jennings et al, 2005;Owusu et al, 2018). We use the aforementioned threshold to identify secondary infections because chlamydia cases are symptomatic compared to other STIs (e.g.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Each chlamydia case in the MDSS was assigned a unique patient identifier. For patients with multiple reported chlamydia infections, a case was considered new if the second reported positive test occurred more than 14 days after the first positive test (Bernstein et al, 2004;Jennings et al, 2005;Owusu et al, 2018). We use the aforementioned threshold to identify secondary infections because chlamydia cases are symptomatic compared to other STIs (e.g.…”
Section: Study Populationmentioning
confidence: 99%
“…Over the past few decades, studies have found that high incidences of STIs are driven by a high prevalence of infection among core groups (Bernstein et al, 2004;Bush et al, 2008;Gesink et al, 2011;Owusu et al, 2018). Core groups often have repeated infections and are associated with commercial sex workers (Nguyen et al, 2009;Neaigus et al, 2016), homosexual men (van Aar et al, 2016) or simply residents of low socioeconomic areas (Thomas et al, 2010;Owusu et al, 2018). These individuals often have structured networks of sexual partnerships with high sexual behaviours (Zenilman et al, 1999;Gunn et al, 2000;Bernstein et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This month we also publish epidemiological studies exploring risk of STI by ethnicity7, ethnicity and socioeconomic status8, along with a meta-analysis of the association between anal intercourse and rectal chlamydia infection in women 9. In a modelling study, Omori and colleagues question the view that HSV potentiates HIV transmission 10…”
mentioning
confidence: 99%